Evaluation of Hung Juries in Bronx County, New York, Los Angeles County, California, Maricopa County, Arizona, and Washington, DC, 2000-2001 - Hannaford-Agor, Paula L. ([Verlag nicht ermittelbar], 2003)
This study was undertaken for the purpose of providing an empirical picture of hung juries. Researchers were able to secure the cooperation of four courts: (1) Bronx County Supreme Court in New York, (2) Los Angeles County Superior Court in California, (3) Maricopa County Superior Court in Arizona, and (4) District of Columbia Superior Court in Washington, DC. The four sites were responsible for distributing and collecting questionnaire packets to all courtrooms hearing non-capital felony jury cases. Each packet contained a case data form requesting information about case characteristics (Part 1) and outcomes (Part 2), as well as survey questionnaires for the judges (Part 3), attorneys (Part 4), and jurors (Part 5). The case data form requested type of charge, sentence range, jury's decision, demographic information about the defendant(s) and the victim(s), voir dire (jury selection process), trial evidence and procedures, and jury deliberations. The judge questionnaire probed for evaluation of the evidence, case complexity, attorney skill, likelihood that the jury would hang, reaction to the verdict, opinions regarding the hung jury rate in the jurisdiction, and experience on the bench. The attorney questionnaire requested information assessing the voir dire, case complexity, attorney skill, evaluation of the evidence, reaction to the verdict, opinions regarding the hung jury rate in the jurisdiction, and experience in legal practice. If the jury hung, attorneys also provided their views about why the jury was unable to reach a verdict. Finally, the juror questionnaire requested responses regarding case complexity, attorney skill, evaluation of the evidence, formation of opinions, dynamics of the deliberations including the first and final votes, juror participation, conflict, reaction to the verdict, opinions about applicable law, assessment of criminal justice in the community, and demographic information.